A New Species of Neotropical Carpenter Ant in the Genus Camponotus (Hymenoptera: Formicidae), Apparently without Major Workers - William Mackay; Paola A. Barriga (Psyche: A Journal of Entomology)
We describe a new species of carpenter ants from Ecuador, which apparently has an obligatory relationship with the ant plants Cecropia membranacea Trécul, C. herthae Diels and C. marginalis Cuatrec. The workers are relatively small and hairy, and based on a number of collections, it does not appear to have major workers. We compare the new species to Camponotus balzani, to which it appears to be similar and which has normal major workers, and also lives in Cecropia spp.